Development and study of interaction trading platform with consumers - Slipko, D.; Khar, A. T. (Видавництво НТУ ДП, 2020)
This article is about website development and analysis. Allow to show the full cycle of sales of goods from the very beginning.
Keywords: веб-сайт; розробка веб-сайтів; торгівельна платформа